The Antioxidant Auraptene Improves Aged Oocyte Quality and Embryo Development in Mice - Yun-Hee Kim; Su-Yeon Lee; Eun-Young Kim; Kyeoung-Hwa Kim; Mi-Kyoung Koong; Kyung-Ah Lee (MDPI AG, 2022)
Decrease in quality of postovulatory aged oocytes occurs due to oxidative stress and leads to low fertilization and development competence. It is one of the main causes that exerting detrimental effect on the success rate in assisted reproductive technology (ART). Auraptene (AUR), a citrus coumarin, has been reported to possess an antioxidant effects in other tissues. In this study, we aimed to confirm the potential of AUR to delay the oocyte aging process by alleviating oxidative stress. Superovulated mouse oocytes in metaphase of second meiosis (MII) were exposed to 0, 1 or 10 μM AUR for 12 h of in vitro aging. AUR addition to the culture medium recovered abnormal spindle and chromosome morphology and mitigated mitochondrial distribution and mitochondrial membrane potential (ΔΨ) in aged oocytes. AUR-treated aged oocytes also showed suppressed oxidative stress, with lower reactive oxygen species (ROS) levels, higher glutathione (GSH) levels and increased expression of several genes involved in antioxidation. Furthermore, AUR significantly elevated the fertilization and embryo developmental rates. Oocytes aged with 1 μM AUR exhibited morphokinetics that were very similar to those of the control group. Altogether, these data allowed us to conclude that AUR improved the quality of aged oocytes and suggest AUR as an effective clinical supplement candidate to prevent postovulatory aging.